Analisis Faktor Determinan Wisatawan Domestik Menggunakan Digital Payment pada Sektor Pariwisata di Kota Yogyakarta - Armida Sari Lubis; Yulfan Arif Nurohman (Syntax Corporation, 2023)
Digital Payment (fintech) is a new variation of business innovation through a combination of financial services and digital-based information technology that changes the financial services business model from manual to automatic through digital technology. With the existence of fintech technology, transaction activities in the community are more practical and effective and assist the community in gaining access to financial products and increasing knowledge about finance. The aim is to find out the determinant factors that influence domestic tourists using digital payments in the Yogyakarta tourism sector. data collection was done by distributing questionnaires to 100 respondents. Data analysis techniques were carried out in several stages, including: validity test, reliability test, and factor analysis. shows that the 4 factors that influence the intention of domestic tourists to use digital payment factors consist of ease of transaction, availability of payment, accessibility of transactions, and benefits. And based on the factor analysis, the dominant influencing variable is the ease of transaction variable.